Potential of 3'-fluoro-3' deoxythymidine as a cellular proliferation marker in PET oncology examination - Hassan, Hishar; Price, Roger; Ahmad Saad, Fathinul Fikri; Lau, Eddie Wing Fai; Carpinelli, Assunta; Nordin, Abdul Jalil (Universiti Putra Malaysia Press, 2016)
Development of the positron emission tomography (PET) diagnostic radiopharmaceutical (18F) fluoro-2-deoxy-D-glucose (18F-FDG) subsequently facilitated the discovery and clinical evaluation of several new tracers as imaging markers for cancer. While 18F-FDG is a widely employed marker forenhanced intracellular glycolysis and metabolic function, one of the newer tracers, (18F)-3'-fluoro-3'deoxythymidine (18F-FLT), has been developed as a biomarker for cell proliferation. In this review, the potential of 18F-FLT as a biomarker for cancer imaging is discussed.